The Pinay as Fun, Fearless Female: Philippine Chick Literature in the Age of the Transnation - Santiago, Katrina Stuart (Humanities Diliman: A Philippine Journal of Humanities; Vol. 6, No. 1&2 (2009), 2010)
The paper analyzes Philippine chick literature by Summit Publishing – the first to come out with local chick literature via the Summit Books – and as a by-product of its magazine Cosmopolitan Philippines. This study delves into chick lit’s existence given these context(s): 1. the dynamics of publication in this country, i.e., the “literary” versus the “popular”, works in English versus works in Filipino, the “artsy” versus the bestseller; 2. the various kinds of feminism(s) of which the middle class Filipina of today is necessarily part; and 3. the facts of globalization and the transnation that are the bases of the Summit Books’ existence, given its links to Cosmopolitan Philippines, and the latter’s existence as a local franchise of a transnational magazine. This paper also looks at the marginalization and suppression that is contingent upon these perspectives of the Summit Books with a view of seeing the possibilities of resistance and rebellion within them. This project uses as backbone contemporary third world feminist and current Philippine cultural theories that insist on the urgent tasks of relevance and involvement that all contemporary cultural productions by women must face. More particularly, this study uses notions of subjectivity and agency, and the processes of negotiation these allow, towards an analysis of where these women’s texts necessarily belong to. This kind of analysis is utilized precisely because these texts traverse across the oppressive and the empowering, the status quo and the possibilities of rebellion, and the powerless and the powerful. In the end, such negotiation is seen as Summit Books’ contribution to the contemporary creation of the Philippine feminine – one that demands that no text be reduced to just its class origins, or just the popular.
Keywords: chick literature, transnation, third world/first world, cosmopolitan, global capital, Philippine feminine